Amplifying Bioactivity of blue honeysuckle (Lonicera caerulea L.) fruit puree through Ultrasonication: Antioxidant and antiproliferative activity - Wei Wu; Xiumei Ma; Yingqi Wang; Yating Yu; Junwei Huo; Dejian Huang; Xiaonan Sui; Yan Zhang (Ultrasonics Sonochemistry)
Blue honeysuckle (Lonicera caerulea L.) serves as a significant reservoir of polyphenol compounds. This impact of ultrasonication processing on the bioaccessibility of blue honeysuckle fruit puree during in vitro digestion was evaluated. The polyphenol compounds, antioxidant capacity and antiproliferative activity were measured, with a particular focus on determining the total proanthocyanidin content of the puree during digestion. The results revealed that the U300 W treatment significantly increased antioxidant content and enhanced the stability of antioxidant capacity, leading to stronger antiproliferative activity. A total of 33 compounds, including 14 phenolic acids, 5 flavanols, 1 flavanol-3-ol, 1 flavanone alcohol, 3 flavanones, 1 flavanone, and 8 non– polyphenols were found in both untreated and ultrasonicated puree during in vitro digestion. The untreated puree contained 22 compounds, while the ultrasonicated puree contained 33. Compared to untreated samples, ultrasonicated samples contained significantly higher levels of loganic acid, dihydrokaempferol, kaempferol derivatives, and plantagoside. Except for vanillic acid, citric acid, protocatechuic acid, and luteolin-4′-O-glucoside, the polyphenols showed a decreasing trend during oral-gastric-small intestinal-colon digestion. The U500 W ultrasonicated fruit puree exhibited the strongest antiproliferative activity. Overall, the results demonstrated that ultrasonication has the potential to enhance the bioaccessibility of antioxidant compounds and the antiproliferative activity of blue honeysuckle fruit puree.